SOSIALISASI DAN PENDAMPINGAN PENGURUSAN NOMOR INDUK BERUSAHA UNTUK PELAKU UMKM - Qurratu'aini, Nafia Ilhama; Muzdalifah, Laily; Novie, Muhafidhah; Taqwanur; Zaki, Achmad; Oktavia, Lily (Journal of Science and Social Development, 2023)
Micro, Small and Medium Enterprises (MSMEs) are currently one of the important sectors supporting the Indonesian economy. Lack of understanding in the meaning of NIB ownership as a legal form for business actors is a problem for MSMEs and also the community. The same problem was also found in MSMEs in Buduran Village, Sidoarjo. The purpose of this community service is to provide direction to business actors regarding preparing and registering to obtain an NIB. This community service begins with location observations, data collection, and implementation of socialization and mentoring activities. After participating in socialization and mentoring, entrepreneurs have a better understanding and are able to manage and have an NIB. It is hoped that this community service can be carried out irrationally for MSME actors in Sidaorjo Regency.